Effect of early intravenous heparin on coronary patency, infarct size, and bleeding complications after alteplase thrombolysis: results of a randomised double blind European Cooperative Study Group trial. Issue 2 (February 1992) - de Bono, D P; Simoons, M L; Tijssen, J; Arnold, A E; Betriu, A; Burgersdijk, C; López Bescos, L; Mueller, E; Pfisterer, M; Van de Werf, F
Abstract : OBJECTIVE--To determine whether concomitant treatment with intravenous heparin affects coronary patency and outcome in patients treated with alteplase thrombolysis for acute myocardial infarction. DESIGN--Double blind randomised trial. TREATMENT REGIMENS--Alteplase 100 mg (not weight adjusted) plus aspirin (250 mg intravenously followed by 75-125 mg on alternate days) plus heparin (5000 units intravenously followed by 1000 units hourly without dose adjustment) was compared with alteplase plus aspirin plus placebo for heparin. SETTING--19 cardiac centres in six European countries. SUBJECTS--652 patients aged 21-70 years with clinical and electrocardiographic features of infarcting myocardium in whom thrombolytic therapy could be started within six hours of the onset of major symptoms. MAIN OUTCOME MEASURE--Angiographic coronary patency 48-120 hours after randomisation. RESULTS--Coronary patency (TIMI grades 2 or 3) was 83.4% in the heparin group and 74.7% in the group given placebo for heparin. The relative risk of an occluded vessel in the heparin treated group was 0.66 (95% confidence interval 0.47 to 0.93). Mortality was the same in both groups. There were non-significant trends towards a smaller enzymatic infarct size and a higher incidence of bleeding complications in the group treated with heparin. CONCLUSIONS--Concomitant intravenous heparin improves coronary patency in patients with alteplase. Whether this can be translated into improved clinical benefit needs to be to be tested in a larger trial.